Introduction To The Hikayat Prang Sabi And Its Relationship To Literature Learning - Julika Lissa Ilhamida; Sumiyadi Sumiyadi Sumiyadi; Rudi Adi Nugroho (STKIP Singkawang, 2025)
Hikayat Prang Sabi is one of the traditional literary works from Aceh that is rich in religious, historical, and patriotic values. This work tells the story of the Acehnese people's struggle against Dutch colonialism, with an emotional narrative that portrays sacrifice and bravery. As a piece of literature, the hikayat holds great potential to be utilized in literary education at schools, particularly in shaping students’ character, introducing local cultural heritage, and enhancing appreciation for the nation's literary legacy. The study of this hikayat aims to explore the core values it contains and relate them to the objectives of modern literature learning. Thus, using texts like Hikayat Prang Sabi can serve as an effective educational medium to instill values of nationalism, religiosity, and love for the homeland in students.